2019
DOI: 10.5513/jcea01/20.2.2143
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of production efficiency and socio-economic factors of organic rice in Sumber Ngepoh district, Indonesia

Abstract: Recently, environmental preservation and the back-to-nature approach to living have become a great lifestyle. The conditions for making organic rice have received a significant amount of attention in the rice market. The study of production efficiency will become substantial to the improvement of organic rice farming to fulfill rice demand. This study investigates the relevant variables which affect the production efficiency of organic rice. The Sumber Ngepoh is one of the largest districts in the rice-produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Family size is an internal factor for farmers to grow. The average family size in this study was 3.77, which is common, meaning that most families in Indonesia have three members (Hidayati et al 2019). Rozaki et al (2020) showed that farmers on Java Island are fewer than those outside Java, such as in Sulawesi.…”
Section: Respondents' Demographymentioning
confidence: 65%
“…Family size is an internal factor for farmers to grow. The average family size in this study was 3.77, which is common, meaning that most families in Indonesia have three members (Hidayati et al 2019). Rozaki et al (2020) showed that farmers on Java Island are fewer than those outside Java, such as in Sulawesi.…”
Section: Respondents' Demographymentioning
confidence: 65%
“…The most commonly used methods for estimating rice productivity are Stochastic Frontier Analysis (SFA) and Data Envelopment Analysis (DEA) [8][9][10]. In contrast to parametric methods, DEA is based on the input-output perspective that does not necessitate the specification of a particular functional form, circumventing potential biases that might arise from choosing an inappropriate production function.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that contract farming is an institutional arrangement used to improve smallholder farmers' market access by providing agricultural raw materials to improve TE [5][6][7][8]. Research studies note that smallholder farmers participate in contract farming to reduce the risk associated with production to processors and put the subject cost burden-i.e., seed, pesticides, and fertilizer-on the processor and/or exporters [9,10]. According to recent studies [5][6][7][8], contract farming offers farmers higher productivity and increases their market access.…”
Section: Introductionmentioning
confidence: 99%